Molecular Dynamics Simulation of Gas Molecules Dissolved in Lubricant under Shear - Tetsuya Okumura (Japanese Society of Tribologists, 2009)
Molecular dynamics simulations were conducted in order to investigate the behaviors of dissolved gas molecules in lubricating film under shear. The lubricants were n-hexane and perfluorohexane, and the dissolved components were hydrogen. When the lubricant film was sheared, the dissolved gas molecules moved, and the number of molecules that adsorb on the solid surfaces increased. Shear induced the diffusion of gas molecules in lubricants. The behaviors of the dissolved molecules were affected by a sliding velocity.